Strategies toward the gold medal: Unveiling the anticipatory processes of junior high school olympiad students in geometry problem-solving - Yudianto, Erfan; Ambarwati, Reza; Lusiana, Fina Yatul; Hayiduerapu, Nihassuna; Zulnaidi, Hutkemri (Jurnal Elemen, 2025)
The National Science Olympiad (NSO) presents significant challenges for most junior high school students. This qualitative study examines the cognitive processes of gold medal-winning students by analyzing their anticipation strategies in solving geometry problems. Employing a descriptive-exploratory approach, we conducted problem-solving tests (using modified NSO geometry questions) and semi-structured interviews with a gold medalist from SMPN 2 Jember. Our findings reveal three distinct anticipation patterns: (1) positive internalized anticipation - intuitive conceptual application yielding correct solutions (e.g., establishing geometric relationships without procedural calculations in Problem 1), (2) negative internalized anticipation - rapid but erroneous assumptions (evident in angle miscalculations in Problem 2), and (3) analytical anticipation - systematic verification through logical reasoning (demonstrated in ∠POR ratio reevaluation). These results provide empirical evidence of how anticipation strategies influence olympiad performance. The study suggests practical interventions including: (1) diagnostic tools for anticipation profiling, (2) teacher training programs to cultivate positive anticipation patterns, and (3) curricular integration of analytical anticipation as metacognitive strategy. For olympiad preparation, we recommend scaffolded problem-solving tasks with structured reflection to transform negative anticipation patterns. Future research should investigate the domain-specificity of these anticipation processes across mathematical disciplines.